Dynamic response modeling of mine water flooding following grouting and rehabilitating of coalbed water-conducting channels - Xin Li; Xiaofeng Xiong; Ge Chen; Zhimin Xu; Weixiao Chen; Yajun Sun (Geoenvironmental Disasters)
Abstract Background To optimize strategies for blocking coalbed aquifer water-conducting channels using grouting techniques.This study addresses dynamic water-blocking challenges in coalbed aquifers by introducing two novel materials—superabsorbent polymers (SAPs) and low-carbon cementitious materials (LCMs)—and developing optimized grouting strategies for hydrogeological pathway sealing. Methods Based on the geological framework of Xinjulong Coal Mine, representative of East China mining conditions,multiscale experimental models were established to replicate three critical water-conducting systems: hydraulicallyconductive faults, karst collapse columns, and mining-disturbed aquifers with stress-induced fractures, with geological features reproduced at a 1:100 proportional scale. Results The results demonstrate that SAPs achieved nearly 100% blocking efficiency in karst collapse columns within18 minutes, showcasing exceptional rapid sealing capability under high hydrodynamic pressure, while LCMs exhibitedhigh efficiency (89.4–91.4%) in sealing faults and mining-disturbed aquifers. These performances significantly surpassedthe predicted 80% reduction in mine water flooding volume. A grouting strategy classification system is proposed,systematically linking material selection to flow rate thresholds, with SAPs recommended for rapid, high-pressurescenarios and LCMs for sustainable fracture grouting applications. Conclusions The findings provide a comprehensive solution for mine water hazard prevention that simultaneously supports sustainable mining practices and contributes to China's ‘Dual Carbon’ environmental goals, offering bothimmediate safety benefits and long-term environmental advantages.